(untitled) (Indian Journal of Public Health Research & Development, 2024)
Introduction: The deficiency of Vitamin D is a widely unacknowledged and disregarded health issue globally. The prevalence of this condition is observed across all age groups and genders, affecting various systems in the body. Objectives: To assess the prevalence of hypovitaminosis D among the adult population and compare vitamin D levels between genders, age groups and geographical locations in patients visiting a secondary care hospital at Dimapur. Methods: A retrospective study was carried out over the period of one year from January 2022 to December 2022 on 665 patients (male: 33%, female: 64%) attending the outpatient and inpatient departments. Vitamin D levels were analyzed using enhanced chemiluminescence (vitros 5600). Results: Out of 665 patients, 90 (14%) were found to be vitamin D deficient, 281 (42%) insufficient, 289 (43%) sufficient and 5 (1%) had toxic levels. Males showed a higher percentage (64%) in the vitamin D deficiency and insufficiency groups as compared with females (46%). In the age group of 42-53 years, a higher percentage of people (57%) were found to be affected with vitamin D deficiency and insufficiency. In the regional distribution of vitamin D status, it is observed that the people in the hilly regions have a higher percentage (61%) of vitamin D deficiency and insufficiency as compared with the valley regions (50%). However, there is no statistical difference in mean vitamin D levels within the deficient, insufficient and sufficient groups between genders, different age groups and geographical regions. Conclusion: The present study carried out on patients from a secondary care hospital at Dimapur, Nagaland, shows that males have a higher percentage in vitamin D deficiency and insufficiency. In the age group of 42-53 years, a higher percentage of people were found to be affected with vitamin D deficiency and insufficiency. The vitamin D status of those living in the hilly region shows a higher percentage of vitamin D deficiency and insufficiency. However, there is no statistical difference in mean vitamin D levels within the deficient, insufficient and sufficient groups between genders, different age groups, and between hilly regions and valley regions.